1995
DOI: 10.1111/j.1365-2621.1995.tb05672.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Stress Effects on Growth of Zygosaccharomyces rouxii from an Intermediate Moisture Papaya Product

Abstract: Stress factors studied included 0.95 a, adjusted with sucrose and glycerol, pH (4.0, 3.5, and 3.0), potassium sorbate (0, 500, 1000, and 1500 ppm) and sodium bisulfite (0, 100, and 150 ppm). These were tested on a strain of Zygosaccharomyces rouxii isolated from an intermediate moisture (IM) papaya product. 2. rouxii was very sensitive to SO,. A combination of 100 ppm SO,, 500 ppm sorbate and pH 4.0 is recommended to prevent spoilage of IM fruits by Z. rouxii. The minimum a, for growth in sucrose-glycerol brot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It has been isolated also from a papaya product of high moisture (a w 0.95). A combination of 100 ppm SO 2 , 500 ppm sorbate and pH ≤4.0 has been recommended to prevent its growth in high moisture fruit products because of its high sensitivity to SO 2 (Tapia de Daza et al, 1995). Vanillin may be a natural alternative for eliminating sulfite addition.…”
Section: Inoculated Microorganismsmentioning
confidence: 99%
“…It has been isolated also from a papaya product of high moisture (a w 0.95). A combination of 100 ppm SO 2 , 500 ppm sorbate and pH ≤4.0 has been recommended to prevent its growth in high moisture fruit products because of its high sensitivity to SO 2 (Tapia de Daza et al, 1995). Vanillin may be a natural alternative for eliminating sulfite addition.…”
Section: Inoculated Microorganismsmentioning
confidence: 99%
“…Earlier, it has been shown that the minimum a w required for growth of Z. rouxii in sucrose‐glycerol broth is 0.62 a w (pH range 3.0, 3.5 and 4.0) in the absence of antimicrobials (Tapia de Daza et al . ). IMF pineapple products that are formulated with a very low a w , which corresponds to a high solute concentration, will prevent the growth of the xerotolerant yeast.…”
Section: Resultsmentioning
confidence: 97%
“…This is in agreement with the findings of Tapia de Daza et al . (), wherein Z. rouxii was found to be very sensitive to SO 2 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of their capability of growth at a low a w (Tapia De Daza et al . ), xerotolerant yeasts can present a spoilage problem in IMF technology resulting in serious economic losses. Of late, many challenging studies investigating the microbial stability of IMF model systems or actual IMF products have been conducted using yeasts (El Halouat and Debevere ; Chen et al .…”
Section: Introductionmentioning
confidence: 99%